Some aspects of enzyme technology / Pat M. Lee - M. Lee, Pat (Biro Penyelidikan dan Perundingan, Institut Teknologi MARA, 1994)
The major concern of biotechnology is to produce products via biotransformation. Biotechnology has been generally accepted as the new technology in the 21st century which will bring a great impact to our everyday life. Enzyme technology is one of the important areas in biotechnology.